PROSES PEMBUATAN MESIN PENYERUT UBI JALAR UNTUK CEKER KREMES KAPASITAS 30 KG/JAM - erwanto, Agus; Nurdiana, Nurdiana (MEKANIK: Jurnal Ilmiah Teknik Mesin, 2017)
This sweet potato wrapping machine is a tool to help the community in sweet potato shrinkage to facilitate the processing process and improve the production process. In its operation, the sweet potato wrapping machine is assisted by several main components, namely: shaft, made using a grating machine, grinding wheel, lathe, manufacturing time (0.45 hours), shaving blade, made using a lathe, hand drill, welding, length of manufacture (9.37 hours) and the frame is made using a machine saw, drill, weld grinding machine, length of manufacture (6.57 hours). The role of the main component is very important, because it needs to be done in a good design and one of them is in terms of shrinkage, where the shaving knife must be able to drag sweet potatoes well and time faster. The purpose of sweet potato shrinkage is to identify materials and models, choose machine tools and tools, plan work steps, analyze the processing time and make a time schedule for each component so that in making this sweet potato wrapping machine works well. From the results of the processing time obtained the fastest time and the longest time the shaft making process (27.37 minutes) while the longest time in the manufacture of shear blade (9.37 hours) by analyzing the results of actual manufacturing time for 24.82 (hours).